2022
DOI: 10.3390/ijms24010227
|View full text |Cite
|
Sign up to set email alerts
|

Asprosin Exerts Pro-Inflammatory Effects in THP-1 Macrophages Mediated via the Toll-like Receptor 4 (TLR4) Pathway

Abstract: Adipose tissue is a dynamic endocrine organ, secreting a plethora of adipokines which play a key role in regulating metabolic homeostasis and other physiological processes. An altered adipokine secretion profile from adipose tissue depots has been associated with obesity and related cardio-metabolic diseases. Asprosin is a recently described adipokine that is released in response to fasting and can elicit orexigenic and glucogenic effects. Circulating asprosin levels are elevated in a number of cardio-metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
(89 reference statements)
1
15
0
Order By: Relevance
“…The increase in the concentration of these cytokines is observed in the state of moderate obesity-related inflammation, and their activity is associated with the development of, for example, insulin resistance [ 21 , 22 ]. At the end of last year, Shabir et al [ 24 ] showed that asprosin activates THP-1 macrophages to release TNF-a, IL-12, IL-8, and IL-1b, which may be at least partly related to the TLR4 pathway and NF-kB activation. In turn, the protective effect of asprosin on macrophages was noticed by Zou et al [ 25 ] in an artheriosclerosis model.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the concentration of these cytokines is observed in the state of moderate obesity-related inflammation, and their activity is associated with the development of, for example, insulin resistance [ 21 , 22 ]. At the end of last year, Shabir et al [ 24 ] showed that asprosin activates THP-1 macrophages to release TNF-a, IL-12, IL-8, and IL-1b, which may be at least partly related to the TLR4 pathway and NF-kB activation. In turn, the protective effect of asprosin on macrophages was noticed by Zou et al [ 25 ] in an artheriosclerosis model.…”
Section: Discussionmentioning
confidence: 99%
“…43 Furthermore, the proinflammatory effects of Asprosin in a variety of tissues has been reported. 44 For instance, Asprosin has been clarified to exacerbate inflammatory response in pancreatic β-cells. 45 TNF-α, IL-1β, and IL-6 regulated by NF-kappaB p65 are classical proinflammatory mediators related to the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…As an initiating factor for NAFLD, aberrant hepatocyte lipid metabolism also contributes to the release of proinflammatory cytokines and inflammatory cell infiltration, further aggravating liver tissue injury 43 . Furthermore, the proinflammatory effects of Asprosin in a variety of tissues has been reported 44 . For instance, Asprosin has been clarified to exacerbate inflammatory response in pancreatic β‐cells 45 .…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, asprosin increases PKC-dependent skeletal muscle inflammation brought on by endoplasmic reticulum stress. 17 Because periodontitis has systemic consequences (like other chronic inflammatory illnesses), it might have an effect on the concentration of circulating asprosin. This study's mean periodontal parameter scores revealed highly significant differences between healthy controls vs. periodontitis, healthy controls vs. periodontitis+STEMI, STEMI vs. periodontitis, and STEMI vs. periodontitis+STEMI.…”
Section: Groupsmentioning
confidence: 99%
“…[13][14][15] According to recent studies, asprosin has a role in the inflammatory reactions of many different cell types. 16,17 To our knowledge, a study examining asprosin levels in periodontitis was not available. Because periodontitis has systemic consequences (like other chronic inflammatory diseases), it affects the levels of circulating asprosin.…”
Section: Introductionmentioning
confidence: 99%